Novel Ellipsoid Chitosan-Phthalate Lecithin Nanoparticles for siRNA Delivery - Saeed, Ramzi Mukred; Abdullah, Mohammed; Ahram, Mamoun; Taha, Mutasem Omar (Frontiers in Bioengineering and Biotechnology, 2021)
Small interfering RNA (siRNA) has received increased interest as a gene therapeutic agent. However, instability and lack of safe, affordable, and effective carrier systems limit siRNA's widespread clinical use. To tackle this issue, synthetic vectors such as liposomes and polymeric nanoparticles have recently been extensively investigated. In this study, we exploited the advantages of reduced cytotoxicity and enhanced cellular penetration of chitosan-phthalate (CSP) together with the merits of lecithin (LC)-based nanoparticles (NPs) to create novel, ellipsoid, non-cytotoxic, tripolyphosphate (TPP)-crosslinked NPs capable of delivering siRNA efficiently. Analogous NPs derived from unmodified chitosan or without TPP were used as controls. The resulting NPs were characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM) and were found to be ca. 180 nm in size, exhibiting novel double-layer shells, with excellent stability at physiological pH and in 10% FBS. MTT assay and confocal fluorescence microscopy showed that CSP-LC-TPP NPs are non-cytotoxic and efficiently penetrate cancer cells in vitro. They achieved 44% silencing against SLUG protein in MDA-MB-453 cancer cells and were significantly superior to a commercial liposome-based transfection agent that achieved only 30% silencing under comparable conditions. Moreover, the CS-LC-TPP and CSP-LC-TPP NPs protected their siRNA cargos in 50% serum and from being displaced by variable concentrations of heparin. In fact, CSP-LC-TPP NPs achieved 26% transfection efficiency in serum-containing cell culture media. Real-time wide-field fluorescence microscopy showed siRNA-loaded CSP-LC-TPP NPs to successfully release their siRNA cargo intracellularly.